Circulating 25-hydroxyvitamin D and survival in women with ovarian cancer. Issue 1 (13th May 2015) - Webb, Penelope M; de Fazio, Anna; Protani, Melinda M; Ibiebele, Torukiri I; Nagle, Christina M; Brand, Alison H; Blomfield, Penelope I; Grant, Peter; Perrin, Lewis C; Neale, Rachel E
ABSTRACT: Background: Vitamin D status might be associated with cancer survival. Survival after ovarian cancer is poor, but the association with vitamin D has rarely been examined. Objective: We evaluated the association between serum 25-hydroxyvitamin D [25(OH)D], a marker of vitamin D status, and ovarian cancer survival. Design: Participants were women with invasive ovarian cancer diagnosed between 2002 and 2005 who participated in the Australian Ovarian Cancer Study. Serum samples, collected at diagnosis ( n = 670) or after completion of primary treatment and before recurrence ( n = 336), were assayed for 25(OH)D. Sociodemographic, dietary, and lifestyle data came from questionnaires self-completed at recruitment, and clinical and survival data were from medical records, supplemented by linkage to the Australian National Death Index (October 2011). Cox proportional hazards regression was used to estimate HRs and 95% CIs for the association between circulating 25(OH)D and survival. Results: Overall, 59% of the women died during follow-up, with 95% of deaths resulting from ovarian cancer. Circulating 25(OH)D concentrations (mean: 44 nmol/L) were significantly associated with age, state of residence, season of blood collection, and body mass index but not with tumor histology, stage or grade, or comorbidities. Higher 25(OH)D concentrations at diagnosis were significantly associated with longer survival (adjusted HR: 0.93; 95% CI: 0.88, 0.99 per 10 nmol/L), but there was no significant association with progression-free survival or for 25(OH)D measured after primary treatment. Conclusions: In our cohort, higher serum 25(OH)D concentrations at diagnosis were associated with longer survival among women with ovarian cancer. If confirmed in other studies, this suggests that vitamin D status at diagnosis may be an independent predictor of prognosis. Furthermore, if the association is found to be causal, improving vitamin D status may improve ovarian cancer survival rates.